(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2012)
Do good, get good, is the new human resource managementmantra. Every bit of the human resource of any organization has to be respectedand bestowed with befitting HRM practices to generate service orientedbehaviours for fantastic and phenomenal success in the global tourism. So, thisstudy has practical and policy implications for the organizations, and serviceorganizations in particular. Organizations can certainly make significantimprovements to their performance by emphasizing excellent human resourcemanagement practices. Research papers, articles, newspapers, books, internetetc. are all flooded with dialogues on globalization. In fact, it is noexaggeration. It is the catch word now-a day. The massive change in the styleand structure of businesses has further strengthened the belief thatglobalization is heading its way for even bigger dimensions and at an everincreasing pace. Economies are witnessing a new face of competition. In afast-paced, globally competitive economy, efforts to boost productivity andquality never end (Cascio, 1998). The Indian government companies need to learnfrom the practices adopted by the private/multinational companies especiallywith regard to competitive compensation, selection and socialization ofemployees, and contemporary HR practices. Gone are the days when experience wasthe basis for deciding seniority, which in turn was the basis for decidingcompensation.